2020
DOI: 10.1108/ijm-04-2020-0156
|View full text |Cite
|
Sign up to set email alerts
|

About sad legacies: a study of the intergenerational occupational legacy in Brazil

Abstract: PurposeThis article aims to analyze the workers' probabilities of following their parents’ occupational legacy and whether these individuals are paid differently compared to those who opted for occupations different from their parents, in Brazil.Design/methodology/approachTo that end, the occupational legacy probability equation was estimated as the quantile wage equations with sample selection bias correction and the wage decomposition for Brazil from the microdata of the National Household Sample Survey (PNA… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(10 citation statements)
references
References 43 publications
0
10
0
Order By: Relevance
“…That is, students with the greatest social vulnerability were the ones who had the highest earnings after attending undergraduate programs. Indeed, increased access to higher education via affirmative action may be an effective mechanism to promote intergenerational mobility, leading the students to achieve levels of socioeconomic status above those of their parents [ 5 , 11 ].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…That is, students with the greatest social vulnerability were the ones who had the highest earnings after attending undergraduate programs. Indeed, increased access to higher education via affirmative action may be an effective mechanism to promote intergenerational mobility, leading the students to achieve levels of socioeconomic status above those of their parents [ 5 , 11 ].…”
Section: Discussionmentioning
confidence: 99%
“…However, this does not reflect reality since socioeconomic inequality remains a challenge in the global human rights agenda [ 1 , 2 ]. Furthermore, the disparities between classes are more pronounced in some countries than others [ 2 5 ]. In this aspect, Brazil is renowned for its persistent socioeconomic and racial inequality stemming from its history of colonization and slavery [ 2 8 ].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Family background is proxied by the father's education (dummy = 1 for those whose father holds a university degree or a higher title) and occupation (dummy = 1 for those whose father has/had a white-collar job). Some studies have demonstrated that families have a strong influence on career choices by their children (Gomes et al , 2020), while others have highlighted that parents might increase individual employment opportunities and occupational outcomes thanks to their networks (Ordine and Rose, 2015). Finally, one dummy variable observes respondents' migration between university graduation and PhD enrollment.…”
Section: Methodsmentioning
confidence: 99%